Malaysian Halal export market: case study on developing countries - Mazlan, Azral Izwan; Hamzah, Hanny Zurina (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2015)
A standard is believed to be one of the factors that will boost international trade. Malaysia is known as a Muslim country worldwide which among the earliest initiated the Halal certification standard. Consequently, the Halal industry evolved and apparently giving Malaysia a comparative advantage in gaining global market share. However the statistics has shown that after three years, the Halal products export growth rate is declining significantly particularly in developing countries. This study aims to identify the determinants of Malaysian Halal export. The findings might be helpful to local Halal industry players to boost their Halal product export. This study employed fixed-effects model of panel data for 44 developing countries for Halal export from 2010 to 2013, GDP of the importer country is proven to be significant factor in enhancing export of Malaysian Halal products.